Peasant utopia : the communalization of class politics in East Bengal, 1920-1947 - Hashmi, Taj Ul-Islam (Dhaka : University Press Limited, 1994)
Social sciences
Keywords: Peasant utopia; Communalization; Class politics; Land tenure; Peasant movement; Rice production; Village community